2019
DOI: 10.21859/ijb.2153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human Recombinant Tumor Necrosis Factor Receptor-2 on Reducing Inflammatory of Collagen -Induced Arthritis in Balb/c Mice

Abstract: Background The tumor necrosis factor alpha (TNFα) is a cytokine that produced principally by monocyte/macrophages and T lymphocytes, respectively. TNFα is recognized as the primary mediator of immunity in inflammation reaction. One important application of Tumor Necrosis Factor Receptor 2 (TNFR2) is for the treatment of autoimmune diseases like rheumatoid arthritis (RA). Objectives The aim of this study is to examine the therapeutic trace of the recombinant humanTNFR2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…At the same time, in the groups that were injected with P-ASA, the number of GRA is increased only at the peak of inflammation, and after 24 hours it is fully normalized, which may be due, on the one hand, to prolongation, and, on the other hand, to immunomodulating properties, that is, with the peculiarities of the action of pectin [9][10][11] . The decrease in the intensity of oxidative processes at the peak of inflammation (5 h after carrageenan injection) under the action of ASA, assessed by the level of malondialdehyde in serum, can be explained by a decrease in the activity of neutrophils as a result of the immunosuppressive effect of ASA 26,27 or by the manifestation of its antioxidant properties which is in agreement with a report 28 . In the groups that were treated with the molecular complex P-ASA, the level of malondialdehyde was not decreased, and when P-ASA was administered at the dose of 200 mg/kg, at the peak of inflammation, malondialdehyde was increased sharply, which may be due to the activation of oxidative processes occurring primarily in neutrophils in response to the injection of an antigen.…”
Section: Influence Of Preparations On Catalase Activity and Malondialsupporting
confidence: 92%
See 2 more Smart Citations
“…At the same time, in the groups that were injected with P-ASA, the number of GRA is increased only at the peak of inflammation, and after 24 hours it is fully normalized, which may be due, on the one hand, to prolongation, and, on the other hand, to immunomodulating properties, that is, with the peculiarities of the action of pectin [9][10][11] . The decrease in the intensity of oxidative processes at the peak of inflammation (5 h after carrageenan injection) under the action of ASA, assessed by the level of malondialdehyde in serum, can be explained by a decrease in the activity of neutrophils as a result of the immunosuppressive effect of ASA 26,27 or by the manifestation of its antioxidant properties which is in agreement with a report 28 . In the groups that were treated with the molecular complex P-ASA, the level of malondialdehyde was not decreased, and when P-ASA was administered at the dose of 200 mg/kg, at the peak of inflammation, malondialdehyde was increased sharply, which may be due to the activation of oxidative processes occurring primarily in neutrophils in response to the injection of an antigen.…”
Section: Influence Of Preparations On Catalase Activity and Malondialsupporting
confidence: 92%
“…Analyzing the results obtained for catalase activity in the groups that were injected with P-ASA, it can be concluded that the complexation of pectin with ASA reduced the effect of ASA on the antioxidant catalase enzyme: on a decrease in its activity at the peak of inflammation and on an increase in its activity after 24 h later on administration, which is especially noticeable at a low dose of P-ASA of 100 mg/kg. In reports 24,28,29 , changes in the level of cytokines TNFα, IL-6, IL-1β, IL-8 are mentioned in conjunction with the study of the intensity of inflammatory reactions.…”
Section: Influence Of Preparations On Catalase Activity and Malondialmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, TNF-α serves a pivotal role in inflammation associated with RA (23). TNF-α is mainly produced by macrophages, neutrophils, natural killer cells and endothelial cells, whilst activated lymphocytes can also produce small levels of TNF-α (24). The presence of TNF-α can also induce the production of other proinflammatory factors, including IL-1, IL-8, IL-6 and matrix metalloproteinases (25).…”
Section: Discussionmentioning
confidence: 99%
“…which considers MDA as an index of inflammation and oxidative stress in BPH patients (48). Inflammatory factor has been investigated in previous studies (49)(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%